ARCHER TAYLOR TO A YOUNG LITERARY FOLKLORIST: AN EXCHANGE OF LETTERS - Monteiro, George (Proverbium - Yearbook, 2012)
After having seen a collection of Portuguese proverbs in Western Folklore in 1963, Archer Taylor initiated a correspondence with the young folklorist George Monteiro who had put together the collection. They exchanged eleven letters over the next decade, the last one mailed by Taylor only weeks before his death in 1973. From this correspondence there emerges a portrait of the senior folklorist’s kind and eager willingness to encourage the younger man’s efforts by offer-ing him specific and detailed advice about contacts, as well as suggesting places and opportunities for collecting.